2022
DOI: 10.3389/fnsyn.2022.1006773
|View full text |Cite
|
Sign up to set email alerts
|

Neocortical layer 5 subclasses: From cellular properties to roles in behavior

Abstract: Layer 5 (L5) serves as the main output layer of cortical structures, where long-range projecting pyramidal neurons broadcast the columnar output to other cortical and extracortical regions of the brain. L5 pyramidal neurons are grouped into two subclasses based on their projection targets; while intratelencephalic (IT) neurons project to cortical areas and the striatum, extratelencephalic (ET) neurons project to subcortical areas such as the thalamus, midbrain, and brainstem. Each L5 subclass possesses distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 125 publications
0
10
0
Order By: Relevance
“…Therefore, it is very likely that the distinct neuron populations underlying feedforward vs. feedback controllability correspond to different classes of excitatory neurons in L5. Indeed, diverse studies in multiple species and brain areas have found that there are two major distinguishable classes of L5 pyramidal neurons: extratelencephalicephalic (ET) and intratelencephalic (IT) [50,51]. Anatomically, ET neurons project to the thalamus, mid-brain, and brainstem, with only modest intra-columnar connectivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is very likely that the distinct neuron populations underlying feedforward vs. feedback controllability correspond to different classes of excitatory neurons in L5. Indeed, diverse studies in multiple species and brain areas have found that there are two major distinguishable classes of L5 pyramidal neurons: extratelencephalicephalic (ET) and intratelencephalic (IT) [50,51]. Anatomically, ET neurons project to the thalamus, mid-brain, and brainstem, with only modest intra-columnar connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Not only do these findings map onto the properties of L5 intra-and extratelencephalic pyramidal neurons, respectively, they intuitively map onto the rotational and amplification dynamics expressed at the population level that we found. Both the non-normality of neural circuits due to Dales law and the distinguishing characteristics of L5 intra-and extratelencephalic neurons are ubiquitous across sensory, cognitive, and motor cortical areas [49,51,50]. As such, there is every reason to believe that similar principles of control will apply throughout cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, mice demonstrate a more adept ability to regulate the activity of ET neurons compared to IT neurons 66 . In contrast, L5 IT cells might compute more diverse information and require increased plasticity 66 CCK+ inputs may confer more precision in the modulation of L5 IT neurons, a phenomenon further reinforced by modulatory pathways 67,68 .…”
Section: Discussionmentioning
confidence: 99%
“…Other neuromodulatory classes can instead promote increases in feedback processing. There is evidence to suggest that neuromodulatory neurotransmitters can directly facilitate the interaction between the apical and basal dendritic trees L5 PT pyramidal cells [91][92][93][94]. Hyperpolarization-activated cyclic nucleotide-gated (HCN) Ih channels typically ensure that the apical and basal dendritic compartments of the L5 PT remain electrically isolated from one another [82,95,96].…”
Section: Shifting Between Feedforward and Feedback Modes In The Cereb...mentioning
confidence: 99%